2017
DOI: 10.4028/www.scientific.net/msf.897.427
|View full text |Cite
|
Sign up to set email alerts
|

4.5 kV SiC Junction Barrier Schottky Diodes with Low Leakage Current and High Forward Current Density

Abstract: High-voltage 4H-SiC Junction Barrier Schottky diodes with a reverse breakdown voltage of over 4.5 kV and a turn-on voltage below 1 V have been fabricated. They achieved a forward current of 5 A at a forward voltage drop of 1.8 V and 20 A at 4.2 V. A low reverse leakage current of 0.3 μA at 1.2 kV and 37 μA at 3.3 kV was measured. The chip size was 7.3 mm x 7.3 mm, the active area 0.25 cm2 and the diode was able to handle a repetitive pulse current density of over 300 A/cm2 without degradation. Floating field r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Junction barrier Schottky (JBS) diodes and vertical diffused metal oxide semiconductor (VDMOS) transistors [2] were fabricated on PL-scanned wafers. Processing details of the JBS diodes were previously described [3]. Fabrication of the VDMOS devices was achieved with these modules: alignment marks, implantation (p well , p + , n + ), post implantation anneal, passivation oxide, gate oxidation, poly-Si gate, inter metal dielectric, metallization and passivation.…”
Section: Experimental Setup and Fabricationmentioning
confidence: 99%
“…Junction barrier Schottky (JBS) diodes and vertical diffused metal oxide semiconductor (VDMOS) transistors [2] were fabricated on PL-scanned wafers. Processing details of the JBS diodes were previously described [3]. Fabrication of the VDMOS devices was achieved with these modules: alignment marks, implantation (p well , p + , n + ), post implantation anneal, passivation oxide, gate oxidation, poly-Si gate, inter metal dielectric, metallization and passivation.…”
Section: Experimental Setup and Fabricationmentioning
confidence: 99%
“…Schottky junction and reduce the leakage current but this also makes them more resistive (26) are made possible by a mature implant and annealing procedure for the p-type dopant. Recently, it was demonstrated that they were able to reproducibly block 4.5 KV (28). In the past it was shown they could block up to 10 KV (29).…”
Section: Crystalline Defectsmentioning
confidence: 99%
“…the PiN part). Promising results, both in terms of on-state performance and ensuring repetitive characteristics among different manufacturing lots, were obtained with the deposition of 100 nm TiAl3 on the front-side and rapid thermal annealing the wafers for 2 min at 980°C [9][10][11].…”
Section: Diodesmentioning
confidence: 99%
“…This work looks at the development of an uncontrolled diode based rectifier, of common use, for instance, in wind power conversion systems, with the ability to handle repetitive current surges of up to some times the nominal on-state current level [8]. So, to make the most of Schottky and p-i-n junction diode features, high voltage 4H-SiC Junction Barrier Schottky (JBS) diodes were designed and fabricated, with a nominal breakdown voltage in excess of 3.3 kV [9]. The devices were packaged in a multi-chip rectifier module configurable as both full-bridge and half-bridge rectifier topology (single phase).…”
Section: Introductionmentioning
confidence: 99%